Modified cement system : Durability and aesthetics - Mohamed, J.S.Z; Razali, I. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study is to prove that by using a modified cement system such as Pulverized Fly Ash (PFA) and Polymers (water based latex grade 29Y46), the efflorescence of the mortar can be prevented. The results from this study proved the modified mortar which is a sample with PFA and Polymers has higher strength, durability and less efflorescence compared with non-modified cement system.